Rhinolithiasis: an unusual cause of sinusitis complicated with frontal osteomyelitis and epidural abscess - Atmaca, Sinan; Belet, Nurşen; Sensoy, Gülnar; Belet, Umit (The Turkish Journal of Pediatrics, 2010)
Rhinoliths are rare foreign bodies of the nose formed by in situ mineralization of endogenous or exogenous foreign material. They are often asymptomatic but may have various clinical presentations, with purulent rhinorrhea and nasal obstruction being the most common. They may go unnoticed for a long period and be diagnosed accidentally during a routine examination. We report a 6.5-year-old girl with rhinolithiasis complicated with sinusitis, frontal osteomyelitis and epidural abscess; she had a history dating back four years.